(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The aim of the research is to explain the nature of the relationship between the dimensions of the strategic recovery of the service represented by (compensation, speed of response, apology, initiative (defining the problem) and the strategic goals of the company represented in (profitability, growth, community service, employee satisfaction) in the National Insurance Company, it has been approved The questionnaire as a tool to collect data and information from the sample of (58) who are in (department manager, M. department director, division official, unit official) and the statistical program (spss) was used in calculating (arithmetic mean, standard deviation, coefficient of variation, coefficient of Correlation, t-test, variance x2) and the research reached a number of conclusions, the most prominent of which were: - There is a strong correlation between the strategic recovery of the service dimensions and the company’s strategic goals, and there are differences in the sample response around the questionnaire paragraphs according to personal variables (age, educational qualification, location Career, number of years of service).